MXene nanocomposites for microwave absorption. Issue 1 (1st May 2022) - Garg, Anuj; Goel, Anshika; Prasher, Sangeeta; Kumar, Rajesh; Moulick, Rakesh
Abstract: The present era of technology and development, more and more electronic devices are used in various feild releasing microwave radiation in environment. These microwave waves can interfere in high precise communication and medical equipments affecting their performance. Although, they ought to be more precise and faster than before, hence microwave absorption in devices is becoming important. Therefore, sheilding and attenuation of microwave has attracted many researchers. Recently, 2D materials such as black phosphorus and graphene coated with transition metal are given a lot of attention in this matter. MXene, a recently discovered material in 2011 is becoming more popular because of its amazing properties such as physical strength, chemical activity, relatively high active surface area and good conductivity. They are proving to be very promising material in microwave absorption and shielding material. Various aspects of MXene nanocomposites for absorption of microwave has been highlighted. Finally, some drawbacks and future prospects related to this promising feild have been outlined.